Catechesis and Catholic Religious Education: Distinct Nonetheless Complementary - Sultana, Carl-Mario (Verbum Vitae, 2020)
Catechesis and religious education are two ways in which the ministry for the education for the faith is exercised, but within different physical contexts and with interlocutors coming from different backgrounds. Moreover, both catechesis and religious education share the same contents, which have been passed on to the interlocutors. This paper seeks to shed some light on the relationship between catechesis and religious education, in terms of their being distinct but at the same time complementary to each other. In this pursuit, we put forward arguments from both directions, those in favour of considering Catholic Religious Education and catechesis as identical and those viewing the two as distinct. The aim is to highlight the specific mission and role of each in education for the faith of the contemporary human being.